Topical EOSSKY fullerene moisturizing and repairing cream for preventing acute radiation dermatitis in breast cancer patients undergoing radiotherapy: a randomized controlled trial - Wang, Qi; Shi, Xiaoning; Guo, Jinli; Gu, Zhanjun; Dong, Xinghua; Qin, Yanxia (Frontiers in Medicine, 2025)
Background and PurposeAcute radiation dermatitis (ARD) is a prevalent complication among breast cancer patients undergoing radiotherapy. Fullerene possesses broad-spectrum free radical scavenging properties, which may be beneficial in mitigating oxidative stress. This study aimed to evaluate the impact of fullerene on both the incidence and severity of ARD in breast cancer patients.MethodsThis study involved 88 breast cancer patients who met the inclusion criteria. Participants were randomly assigned to either the fullerene group or the control group in a 1:1 ratio. The primary endpoint was the grading of ARD and the cumulative dose of ionizing radiation at the first occurrence of ARD. Secondary endpoints included patient-reported symptoms, such as pain and quality of life (QoL).ResultsThe Radiation Therapy Oncology Group (RTOG) score was significantly lower in the fullerene group than in the control group, and the cumulative dose of ionizing radiation at the first occurrence of ARD was higher. There was a statistically significant difference between the two groups (P < 0.05). Regarding the secondary endpoints, the pain scores exhibited a significant reduction in the fullerene group as compared with the control group (P < 0.05). The results of the Skindex-16 scale showed that the quality of life was better in the fullerene group than in the control group (P < 0.01).ConclusionThis trial indicated that fullerene could reduce the grading of ARD, delay the occurrence of ARD, alleviate patients’ symptoms, and improve the patients’ overall quality of life.Clinical trial registrationhttps://www.chictr.org.cn/index.html, identifier CTR2400079800.